Evaluasi Pelayanan Kefarmasian di Puskesmas Kabupaten Ponorogo - Norcahyanti, Ika; Hakimah, Farda; Christianty, Fransiska Maria (Journal of Islamic Pharmacy, 2020)
Public health center is a primary health facility, and pharmacy services support its activities. Periodic monitoring and evaluation of activities are needed to assure the quality of pharmaceutical services. Pharmacy personnels can evaluate pharmaceutical services at the public health center using a guideline published in 2008 by the Directorate of Pharmacy and Community Clinics of the Indonesian Ministry of Health. The purpose of this study was to determine the characteristics, description, and quality of pharmaceutical services at the public health centers in Ponorogo after being evaluated using a list of pharmaceutical services in 2008. This research was an observational survey on all pharmacy personnels and other personnels responsible for the pharmacy room at the public health center in Ponorogo. The analysis of data was using descriptive techniques. The results show that the public health centers were mostly an inpatient center (n=19; 61.3%) and accredited â€˜madyaâ€™ (n=22; 71%). Morover, the head of a pharmacy room was dominantly a pharmacy technician (n=24; 77.4%). Pharmaceutical services generally fulfilled the supporting for and quality control indicators. However, several indicators did not fully meet the guideline, including clinical judgements, counseling, and home care. Overall, only three public health centers can be rated â€œgoodâ€ in delivering quality pharmaceutical services, whilst the other eight and twenty were rated â€œmoderateâ€ and â€œlessâ€, respectively.